PERANCANGAN KONDENSOR ALAT PENYULING BIOETANOL KAPASITAS 20 TON NIRA / HARI - Mufti, Moch.; Santoso, Iwan Bagus (MEKANIKA: Jurnal Teknik Mesin, 2015)
Bioethanol (C2H5OH) is a one biofuel the present as alternative fuels more environmentally friendly and nature the renewable. The alternative fuel is processed from plants that has the advantage of being able to lose shareof CO2 emissions Up to 18%, compared with stock emissions fossil fuels such as kerosene (Anonymous, 2007a).Bioethanol can be produced from various raw materials, Many are in Indonesia, only prayer is Sorghum. So it is verypotential processed for review and developed because raw material is very well known.The principle is simple distillation of ethanol is separating air by its boiling point. Pure ethanol boiling temperatureof 79oC, while the pure air boils at 100oC. When the lack of ethanol-water mixture is heated, then at ambienttemperature 79oC ethanol will already boil and evaporate, while the air yet. With set temperature we can separateair between the steam ethanol.Keywords: Bioethanol, Sorghum, distillation